THE INFLUENCE OF THE SOCIAL ENVIRONMENT ON ATTITUDE RATIONAL ECONOMY THROUGH LIFESTYLE FOR STUDENTS OF VOCATIONAL SCHOOL 2 BLITAR - Ahmad, Asrori; Anas, M.; Sugiyono, Sugiyono (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study explores the influence of social environment on the consumption behavior of vocational school students, which is also influenced by their lifestyle. This study uses a quantitative approach with correlational techniques and path analysis, assisted by SPSS 19.0 and Smart PLS programs. The findings show that the social environment has a significant influence on lifestyle, which then affects students' rational economic attitudes. Lifestyle acts as a mediator between the social environment and economic attitudes, indicating the importance of a holistic approach in understanding and improving students' economic well-being. The results of this study provide guidance for educational institutions and policy makers to develop more targeted strategies in improving students' financial literacy and economic behavior, by considering non-academic factors and encouraging healthy living habits and a strong understanding of financial management.